Cell secretome based approaches in Parkinson's disease regenerative medicine. (2nd December 2018) - Marques, Cláudia R.; Marote, Ana; Mendes-Pinheiro, Bárbara; Teixeira, Fábio G.; Salgado, António J.
ABSTRACT: Introduction : The available therapeutic strategies for Parkinson's disease (PD) rely only on the amelioration of the symptomatology of the disease, lacking neuroprotection or neuroregeneration capacities. Therefore, the development of disease modifying strategies is extremely important for the management of PD in the long term. Areas covered : In this review, the authors provide an overview of the current therapeutic approaches for PD and the emerging use of stem cell transplantation as an alternative. Particularly, the use of the secretome from mesenchymal stem cells (MSCs), as well as some methodologies used for the modulation of their paracrine signaling, will be discussed. Indeed, there is a growing body of literature highlighting the use of paracrine factors and vesicles secreted from different cell populations, for this purpose. Expert opinion : Secretome from MSCs has shown its potential as a therapy for PD. Nevertheless, in the coming years, research should focus in several key aspects to enable the translation of this strategy from the bench to the bedside.